TRADE OFF THEORY DAN KECEPATAN PENYESUAIAN KE ARAH TARGET LEVERAGE (SUATU TINJAUAN TEORITIS DAN EMPIRIS) - Cahyaningdyah, Dwi (BISMA (Bisnis dan Manajemen), 2018)
Trade off theory of capital structure predicts that firms have optimal target leverage. However, empirical studies provide evidence that firms capital structure often deviate from the target because of economic shocks. Therefore firm should make adjustment toward target leverage to maintain optimal trade off between cost and benefit of their financing decision. Understanding of adjustment behavior of the firm is key factor to comprehend firms capital structure dynamic. Nevertheless, asan important issue in corporate finance, speed of adjustment estimation still have several problems caused bias and spurious result. Recent studies identified several econometric problems of the model used by previous studies. This paper revisited these problems and provide several alternative solutions from recent studies.